Fibromyalgia is associated with hypersensitivity but not with abnormal pain modulation: evidence from QST trials and spinal fMRI - Staud, Roland; Godfrey, Melyssa M.; Stroman, Patrick W. (Frontiers in Pain Research, 2023)
Widespread pain and hyperalgesia are characteristics of chronic musculoskeletal pain conditions, including fibromyalgia syndrome (FM). Despite mixed evidence, there is increasing consensus that these characteristics depend on abnormal pain augmentation and dysfunctional pain inhibition. Our recent investigations of pain modulation with individually adjusted nociceptive stimuli have confirmed the mechanical and thermal hyperalgesia of FM patients but failed to detect abnormalities of pain summation or descending pain inhibition. Furthermore, our functional magnetic resonance imaging evaluations of spinal and brainstem pain processing during application of sensitivity-adjusted heat stimuli demonstrated similar temporal patterns of spinal cord activation in FM and HC participants. However, detailed modeling of brainstem activation showed that BOLD activity during “pain summation” was increased in FM subjects, suggesting differences in brain stem modulation of nociceptive stimuli compared to HC. Whereas these differences in brain stem activation are likely related to the hypersensitivity of FM patients, the overall central pain modulation of FM showed no significant abnormalities. These findings suggest that FM patients are hyperalgesic but modulate nociceptive input as effectively as HC.